A recipe for designing water-soluble, beta-sheet-forming peptides. - Mayo, K. H. (Cold Spring Harbor Laboratory Press, 1996)
Based on observations of solubility and folding properties of peptide 33-mers derived from the beta-sheet domains of platelet factor-4 (PF4), interleukin-8 (IL-8), and growth related protein (Gro-alpha), as well as other beta-sheet-forming peptides, general guidelines have been developed to aid in the design of water soluble, self-association-induced beta-sheet-forming peptides. CD, 1H-NMR, and pulsed field gradient NMR self-diffusion measurements have been used to assess the degree of folding and state of aggregation. PF4 peptide forms native-like beta-sheet tetramers and is sparingly soluble above pH 6. IL-8 peptide is insoluble between pH 4.5 and pH 7.5, yet forms stable, native-like beta-sheet dimers at higher pH. Gro-alpha peptide is soluble at all pH values, yet displays no discernable beta-sheet structure even when diffusion data indicate dimer-tetramer aggregation. A recipe used in the de novo design of water-soluble beta-sheet-forming peptides calls for the peptide to contain 40-50% hydrophobic residues, usually aliphatic ones (I, L, V, A, M) (appropriately paired and mostly but not always alternating with polar residues in the sheet sequence), a positively charged (K, R) to negatively charged (E, D) residue ratio between 4/2 and 6/2, and a noncharged polar residue (N, Q, T, S) composition of about 20% or less. Results on four de novo designed, 33-residue peptides are presented supporting this approach. Under near physiologic conditions, all four peptides are soluble, form beta-sheet structures to varying degrees, and self-associate. One peptide folds as a stable, compact beta-sheet tetramer, whereas the others are transient beta-sheet-containing aggregates.